Information-processing, support and coping: breast cancer patients and their experiences with a mentor and CHESS - Farrell, Brittany (University of Wisconsin--Whitewater, 2012)
After a positive cancer diagnosis, the methods used to seek information, support, cope, and process one’s illness can heavily impact one’s outlook on the treatment/recovery process. Improving the quality of doctor-patient interaction and easing anxiety during treatment are two prominent goals within the medical industry. The rise of technology in healthcare has seen the development of electronic health communication sites serving as portals of information and sources of support for patients as they battle diseases. The goal of this study was to compare information-processing behavior, recall of information, and coping techniques of breast cancer patients assigned a mentor, with that of breast cancer patients assigned to a mentor and granted access to an interactive cancer communication website known as CHESS. This study utilized data by Hawkins et al. (2011), in which breast cancer patients were split into either a mentor-only group, or a mentor and CHESS group. Participants were recruited from three U.S. medical centers. A total of 211 women participated in the study; 106 of them were assigned to the mentor-only condition, while the remaining 105 women received a mentor and access to CHESS (Hawkins et al., 2011). The mentor had 10 scheduled calls over six months with participants in both groups. She also utilized email if it was more convenient for the women. Patients were free to write or call her as frequently (or infrequently) as they desired. Each time the mentor emailed or called a participant, she recorded the vi. conversation and took notes on what was discussed. The notes were analyzed for this study; several of the key topics identified were spirituality and religiosity, coping, support, depression, information-seeking behavior and death. The CHESS/Mentor combination provided action-facilitating and nurturing support for its users. There was no firm support for differences in coping abilities between the two groups. There was no evidence to suggest differences in information-seeking behavior by the groups. Several women in either group practiced avoidance behavior when it came to support and information-seeking techniques. Healthcare providers must take into account that patients may desire to pace themselves when receiving traumatizing information about a disease.
This file was last viewed in Adobe Acrobat Pro.
Keywords: Breast--Cancer--Patients; Information behavior; Mentoring; Breast--Cancer--Computer network resources